2011
DOI: 10.1371/journal.pone.0025358
|View full text |Cite
|
Sign up to set email alerts
|

The SOCS2 Ubiquitin Ligase Complex Regulates Growth Hormone Receptor Levels

Abstract: Growth Hormone is essential for the regulation of growth and the homeostatic control of intermediary metabolism. GH actions are mediated by the Growth Hormone Receptor; a member of the cytokine receptor super family that signals chiefly through the JAK2/STAT5 pathway. Target tissue responsiveness to GH is under regulatory control to avoid excessive and off-target effects upon GHR activation. The suppressor of cytokine signalling 2 (SOCS) is a key regulator of GHR sensitivity. This is clearly shown in mice wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 48 publications
3
70
0
Order By: Relevance
“…SOCS2 deficient mice display about 50% increased body size primarily due to the loss of negative regulation of growth hormone (GH) receptor function [42]. SOCS2 negatively regulates the GH receptor through ubiquitination-dependent degradation [43]. SOCS2 was also found to interact with IGF1R and INSR, and this interaction occurred only when the receptor was activated [34,44] suggesting that similar to SOCS1 the interaction between receptor and SOCS2 is mediated through receptor phosphotyrosine residues and the SOCS2 SH2 domain.…”
Section: Socs2mentioning
confidence: 99%
“…SOCS2 deficient mice display about 50% increased body size primarily due to the loss of negative regulation of growth hormone (GH) receptor function [42]. SOCS2 negatively regulates the GH receptor through ubiquitination-dependent degradation [43]. SOCS2 was also found to interact with IGF1R and INSR, and this interaction occurred only when the receptor was activated [34,44] suggesting that similar to SOCS1 the interaction between receptor and SOCS2 is mediated through receptor phosphotyrosine residues and the SOCS2 SH2 domain.…”
Section: Socs2mentioning
confidence: 99%
“…SOCS2-deficient mice exhibit 30-40% increased growth when compared with wild-type littermates as a result of dysregulated growth hormone receptor (GHR) signalling (41). Deletion of the SOCS2-SOCS box abrogates regulation of GH signalling, with SOCS2 shown to have E3 ligase activity, ubiquitinating the GHR in vitro (34,42). SOCS2 has also been shown to bind phosphorylated Pyk2 in NK cells, and this interaction correlates with decreased Pyk2 levels (43).…”
Section: Sh2 Domain Socs Box Proteinsmentioning
confidence: 99%
“…We have demonstrated that SOCS2 targets the growth hormone receptor for ubiquitination whereas SOCS6targets both the c-Kit and Flt3 tyrosine kinase receptors (4,5). SOCS1 has been shown to promote the ubiquitination of JAK2, and VHL is responsible for the ubiquitination and degradation of HIF1␣ (6,7).…”
mentioning
confidence: 98%